2020
DOI: 10.5140/jass.2020.37.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Development of Forecast Algorithm for Coronal Mass Ejection Speed and Arrival Time Based on Propagation Tracking by Interplanetary Scintillation g-Value

Abstract: We have developed an algorithm for tracking coronal mass ejection (CME) propagation that allows us to estimate CME speed and its arrival time at Earth. The algorithm may be used either to forecast the CME’s arrival on the day of the forecast or to update the CME tracking information for the next day’s forecast. In our case study, we successfully tracked CME propagation using the algorithm based on g-values of interplanetary scintillation (IPS) observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…With respect to a real-time CME event that happened on October 2, 2000, the developed algorithm predicted the propagation of three daily storms; the errors in arrival time and speed were 18 minutes and 20 km/s, respectively. This demonstrated that the g-values of IPS observations from the Institute for Space-Earth Environmental Research (ISEE) can be used to track the propagation of CMEs.Furthermore, statistical validation was carried out on 50 CME-ICME pair events, yielding an average error of 310 km/s for velocity and 11.14 h for arrival time[4].Kim & Chang[5] looked into the relationships between solar variability and teleconnection indices, which affect atmospheric circulation and the spatial distribution of the global pressure system, in order to investigate the potential role of the Sun in understanding natural climate change. Using teleconnection indices [Southern Oscillation Index (SOI), Arctic Oscillation (AO), Antarctic Oscillation (AAO), and Pacific-North American (PNA)], they have computed the normalized cross-correlations of the total sunspot area, total sunspot number, and the solar north-south asymmetry.Consequently, (1) El Niño episodes most likely happen three years after a solar maximum because the SOI index has an anti-correlated relationship with both solar activity and the solar north-south asymmetry, with a lag of approximately −3 years.…”
mentioning
confidence: 99%
“…With respect to a real-time CME event that happened on October 2, 2000, the developed algorithm predicted the propagation of three daily storms; the errors in arrival time and speed were 18 minutes and 20 km/s, respectively. This demonstrated that the g-values of IPS observations from the Institute for Space-Earth Environmental Research (ISEE) can be used to track the propagation of CMEs.Furthermore, statistical validation was carried out on 50 CME-ICME pair events, yielding an average error of 310 km/s for velocity and 11.14 h for arrival time[4].Kim & Chang[5] looked into the relationships between solar variability and teleconnection indices, which affect atmospheric circulation and the spatial distribution of the global pressure system, in order to investigate the potential role of the Sun in understanding natural climate change. Using teleconnection indices [Southern Oscillation Index (SOI), Arctic Oscillation (AO), Antarctic Oscillation (AAO), and Pacific-North American (PNA)], they have computed the normalized cross-correlations of the total sunspot area, total sunspot number, and the solar north-south asymmetry.Consequently, (1) El Niño episodes most likely happen three years after a solar maximum because the SOI index has an anti-correlated relationship with both solar activity and the solar north-south asymmetry, with a lag of approximately −3 years.…”
mentioning
confidence: 99%